2016
DOI: 10.21767/2572-5483.100006
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Risk Behavior and Its Change among HIV-Positive Persons after Notifying their HIV Infection Status: A Retrospective Survey

Abstract: Background: The number of People Living with HIV/AIDS (PLWHA) is increasing by year, and sexual transmission accounts for the main route of transmission. While there is some debate on whether notifying HIV infection status will affect PLWHAs' sexual behavior in China, this study investigates sexual risk behavior and its change among PLWHA before and after they are informed of HIV infection and provide evidence for prevention and control of AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…The high proportions of participants with past STI and past TB who never tested for HIV and who did not know where to test indicate that considerable opportunities have been missed for early HIV detection and treatment during contacts with health services, and that integrated care of infectious diseases should be strengthened. Also, as it has been acknowledged, HIV early diagnosis can help prevent onward HIV transmission and acquisition of other STI through the adoption of protective behaviors after notification of HIV infection [39]. In fact, our findings show that HIV-positive participants were more likely to report consistent condom use, reflecting the potential benefits of HIV testing and counselling, as well as follow-up provided at health services in terms of secondary prevention.…”
Section: Discussionmentioning
confidence: 51%
“…The high proportions of participants with past STI and past TB who never tested for HIV and who did not know where to test indicate that considerable opportunities have been missed for early HIV detection and treatment during contacts with health services, and that integrated care of infectious diseases should be strengthened. Also, as it has been acknowledged, HIV early diagnosis can help prevent onward HIV transmission and acquisition of other STI through the adoption of protective behaviors after notification of HIV infection [39]. In fact, our findings show that HIV-positive participants were more likely to report consistent condom use, reflecting the potential benefits of HIV testing and counselling, as well as follow-up provided at health services in terms of secondary prevention.…”
Section: Discussionmentioning
confidence: 51%
“…A retrospective survey conducted among PLWHA, who had been notified their HIV-positive status for more than 6 months in Hunan, China showed that among those who had risky sex, about 50% subjects had more than 1 sexual partner before notification 21 . After notification, the proportions of subjects who had more than 1 sexual partner decreased by 36.9% 21 .…”
Section: Number Of Sexual Partnersmentioning
confidence: 99%
“…A retrospective survey conducted among PLWHA, who had been notified their HIV-positive status for more than 6 months in Hunan, China showed that among those who had risky sex, about 50% subjects had more than 1 sexual partner before notification 21 . After notification, the proportions of subjects who had more than 1 sexual partner decreased by 36.9% 21 . Anonymous surveys in South Africa completed by 413 HIV-positive men and 641 HIV-positive women sampled from HIV/AIDS services revealed that, people who had not disclosed their HIV status to partners reported more sex partners and reported more unprotected vaginal and anal intercourse than people who had disclosed 17 .…”
Section: Number Of Sexual Partnersmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature showed that heterosexual PLHIV tend to adopt safer sex behaviors after HIV diagnosis (Bernier et al, 2016;Lin et al, 2013;Venkatesh et al, 2011;Zhou et al, 2016). Despite emerging data showing gender differences in sexual behavior changes after HIV diagnosis (Bernier et al, 2016;Lin et al, 2013;Weinhardt, 2005), few have explored gender specific correlates of such changes.…”
Section: Introductionmentioning
confidence: 99%